Principles of human movement - Fister, I.; Fister Jr., I.; Fister, D. (Computational intelligence in sports, 2018)
Movement is one of the more complex human functions requiring multiple biological systems in the body to operate in concert. There are five systems that enable the functioning of the organism: skeletal, muscular, nervous, respiratory, and cardiovascular. The first three create a so-called kinetic chain that is responsible for performing the function of movement, while the remaining two supply oxygen and nutrition to the body on the one hand, while removing waste products from the body on the other. The last two systems create a so-called supply chain.